Wideband millimeter-wave substrate integrated waveguide cavity-backed antenna for satellites communications - AL-Fadhali, Najib; A. Majid, Huda; Omar, Rosli; Ismail, M. F.; Rahim, M. K. A.; O. Mumin, Abdulrashid; Esmail, B. A. F. (Institute of Electrical and Electronics Engineers Inc. (ieee), 2020)
This paper presents a new type of wideband waveguide (SIW) cavity-backed patch antenna for millimeter wave (mmW). The antenna proposed applies to applications of 31-36 GHz Ka-band such as satellites communications. The SIW is intended with settings for particular slots. The antenna is constructed on Rogers RT5880 (lossy) with 2.2 dielectric constant, l.27 mm thickness, and 0.0009 loss tangent. It is simulated in the programming of computer simulation technology (CST) Microwave Studio. The simulated results show that the SIW antenna resonates across 31 to 36 GHz bands, which means that this new antenna covers all applications within this range. The reflection coefficients in targeting range are below 10 dB. The antenna achieves good efficiency and gain with 80% and 8.87 dBi respectively.